2015
DOI: 10.1038/srep14380
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms of PCSK2 are associated with glucose homeostasis and progression to type 2 diabetes in a Chinese population

Abstract: Proprotein convertase subtilisin/kexin type 2 (PCSK2) is a prohormone processing enzyme involved in insulin and glucagon biosynthesis. We previously found the genetic polymorphism of PCSK2 on chromosome 20 was responsible for the linkage peak of several glucose homeostasis parameters. The aim of this study is to investigate the association between genetic variants of PCSK2 and glucose homeostasis parameters and incident diabetes. Total 1142 Chinese participants were recruited from the Stanford Asia-Pacific Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 50 publications
1
14
0
Order By: Relevance
“…Global KO Fasting hypoglycaemia, lowered IPGTT glycemia, lack mature glucagon, αand δ-cell hyperplasia, elevated des-31, 32 proinsulin and intact proinsulin [35][36][37][38] Cpe Global KO Obesity, hyperglycaemia, neurological defects, hyperleptinemia 39,40 Cpe HbA1c. 25 Further intronic SNPs have been tied to increased T2D risk (rs2021785), 22 lowered T2D risk 24 and no T2D risk, despite associations with elevated area under the curve of plasma insulin and glucose during OGTT 24 (Table 1).…”
Section: Pcsk2mentioning
confidence: 99%
“…Global KO Fasting hypoglycaemia, lowered IPGTT glycemia, lack mature glucagon, αand δ-cell hyperplasia, elevated des-31, 32 proinsulin and intact proinsulin [35][36][37][38] Cpe Global KO Obesity, hyperglycaemia, neurological defects, hyperleptinemia 39,40 Cpe HbA1c. 25 Further intronic SNPs have been tied to increased T2D risk (rs2021785), 22 lowered T2D risk 24 and no T2D risk, despite associations with elevated area under the curve of plasma insulin and glucose during OGTT 24 (Table 1).…”
Section: Pcsk2mentioning
confidence: 99%
“…While intronic PCSK2 variants are present at minor allele frequencies (MAF) of up to 8% [16], exonic variants are extremely rare in the outbred population. Fourteen putative missense variants were identified in the NHLBI Exome Sequencing Project (ESP), T2D-Genes, and 1000Genomes phase 1 databases (C18G, R47S, E52K, A77D, R81C, D123N, N221D, P244Q, A267T, A385V, R430W, M525V, T569I, and Q595L).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have found both positive and negative associations between intronic variants in PCSK2 and increased T2D risk [13, 14, 1618]. Since coding variants in PCSK2 are very rare in outbred populations, no information exists on whether variants confer a loss or gain of function for this enzyme.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations